Application of The Principle of Justice in Cases of Transfer of Land Rights Based on A Sales Receipt - Gusti Ngurah Darmawan; Anifatus Sa’adah; Gabriel Dito More Sambe Gana; Albertus Yoseph Nahak (NOTARIIL Jurnal Kenotariatan, 2026)
Underhand land sales transactions evidenced only by simple sales receipts as proof of payment often give rise to legal issues in Indonesian society. This research uses a normative juridical method with a statutory approach and case studies of court decisions related to land sales disputes based solely on sales receipts. This research aims to analyze the position of sales receipts as evidence in proving the transfer of land rights, as well as the application of the principle of justice in the transfer of land rights based on receipts. The results of the study indicate that receipts only serve as underhand deeds with limited evidentiary power, namely as proof of payment or the existence of a sales and purchase agreement, but cannot be used as a direct basis for registering the transfer of land rights at the land office. However, in practice, the court can recognize the validity of land sales based on receipts as long as the valid conditions of the agreement according to Article 1320 of the Civil Code are met. Thus, receipts can function as supporting evidence in civil disputes, but do not replace the obligation to make a PPAT deed as a formal requirement for the transfer of land rights.